IMPLEMENTATION SUSTAINABLE ECOTOURISM CIKOLELET TOURISM VILLAGE - Juliana Juliana; Ira Brunchilda Hubner; Diena M Lemy; Rudy Pramono; Sisilia Chelsye Parera; Wilhelmina Rosse Marisca Gajeng (LPPM Institut Pendidikan Nusantara Global, 2023)
Ecotourism is a sustainable and responsible form of travel that promotes conservation, benefits local communities, and provides travelers with a unique and educational experience in natural environments. Although some tourism researchers have used the MOA model to study factors influencing community participation, there is still a scarcity of literature that can provide sufficient empirical support to prove the MOA model's predictive power for examining community participation in the tourism context. Especially in the context of nature tourism. Seeing this gap, the purpose of this research is to determine the impact of sustainable ecotourism on community participation using the MOA model.. This research was conducted in Cikolelet Tourism Village. There were participants whose information was examined by researchers, namely the head of the Cikolelet Tourism Village Pokdarwis and the Village Head and members of the Pokdarwis. The result show that the prospects to implementing sustainable ecotourism in Cikolelet rural tourism area can develop and promote community participation